E-learning and the Educational Organizations Structure Reengineering (EOSR) - Alshara, Osama Khalid; Alsharo, Mohamad Khalid (International Journal of Emerging Technologies in Learning (iJET), 2007)
There are many calls for innovative learning methods that utilize advanced technologies. However, we will raise fundamental questions that look deep into the future of the educational organization. Can the educational institute survive without adapting learning technologies? Would the educational institute succeed in adapting new learning technologies without changing its organizational structure and processes? We claim that the answer to both questions is no. Our research will present the need for educational institutes to incorporate learning technologies and focuses on the demand for the educational organization structure reengineering as a basic requirement for the success of incorporating learning technologies. Our study explores the faculty requirements and policies and procedures of educational institutes in the UAE. The paper concludes with some discussions on findings from a case study of the need of educational organization struc-ture reengineering as a basic requirement for incorporating learning technologies.